الاستثمار في رأس المال البشري كخيار استراتيجي لتحقيق الجودة الشاملة - عزيزي, زهرة; بن صويلح, ليليا (جامعة الوادي - University of Eloued, 2021)
تعد كل من سياسة الاستثمار في رأس المال البشري والجودة الشاملة من أهم الأساليب الإدارية الحديثة التي تمكن المنظمات من تحقيق استمرارها وصنع تميزها في ظل تغيرات متسارعة تميز البيئة الخارجية تستدعي العمل بكفاءة ضمن سياق تنظيمي شديد المنافسة يؤمن بفكرة أن لا بقاء إلا للأقوى المتمكن. تندرج هذه الدراسة في الدائرة التحليلية، وتهدف لمناقشة علاقة التأثير القائمة بين الاستثمار في رأس المال البشري وتحقيق ثقافة الجودة الشاملة في النسق التنظيمي، تم توظيف المنهج الوصفي لتحليل ابعاد هذه العلاقة ومتغيراتها. توصلت الدراسة أن هناك أربعة مجالات أساسية يؤثر من خلالها استثمار رأسمال البشري في تحقيق الجودة الشاملة، ويتعلق الأمر ب: التمكين الذي ينمي الفكر الإبداعي، التحفيز الذي يخلق الإيجابية ويدفع لإتقان العمل، التدريب الذي يكرس الأداء العلمي للمهام، ثم رعاية المورد البشري التي تضمن الولاء وتراكمية المعارف. Abstract: Both the investment policy in human capital and the total quality are among the most important modern management strategies that make the institution succeed in ensuring its continuity as well as its superiority, especially within an external environment that believes in the values of competition and that only the strongest survive This study belongs within the analytical circle, and it aims to analyze the impact relationship existing between investing in human capital and achieving a culture of total quality. The descriptive approach has been employed to analyze the dimensions of this relationship and its variables. The study found that there are four areas through which the investment of human capital affects the achievement of comprehensive quality, and they are related to empowerment, motivation, training, taking care of human resource requirements.
Investing in human capital as a strategic choice to achieve total quality.
مقال
Keywords: استثمار في رأس المال البشري ، اقتصاد المعرفة ، تحفيز ، تمكين ، جودة شاملة; empowerment , Total Quality, Investment in human capital , Motivation , the knowledge economy